Behavioural response patterns on the organisational factors influencing compliance behaviour of business zakat / Mohd Rahim Khamis - Khamis, Mohd Rahim (Academy of Contemporary Islamic Studies, 2016)
Organisational factors and compliance behaviour of business zakat have a significant relationship as revealed by a number of studies. However, lack of study focused on respondents' response on the organisational factors influencing compliance behaviour of business zakat. Hence, the main objective of this study is to investigate the behavioural response patterns on the organisational factors influencing compliance behaviour of business zakat. A total of 276 questionnaires were collected from SMEs entrepreneurs in Selangor. The Rasch Measurement Model was employed to analyse the data. The results showed Person Item Distribution Map (PIDM) illustrates 46 percent of owners of SMEs complies with paying business zakat while 54 percent denoting the group that did not comply with paying business zakat. The finding of this study implies the significance of Rasch Measurement Model in explaining the patterns of respondents' response is able to explain organisational factors influencing compliance behaviour of business zakat among SMEs. This study suggests that future research in the same area to employ Rasch Measurement Model as this method is suitable to analyse items and respondents of a study.